Understanding Mental Health: A Review for Psychiatric Nursing Practice - Sumit Dadaji Khare (Innovational: Journal of Nursing and Healthcare, 2025)
Mental health is a critical component of overall well-being, encompassing emotional, psychological, and social dimensions. This review explores the evolving concepts of mental health, emphasizing definitions from the World Health Organization and DSM-5. It highlights the growing significance of psychiatric nursing in the assessment, management, and advocacy of mental health care across various settings. Historical perspectives, shifts from institutional to community-based care, and a comprehensive overview of common mental health disorders are examined. The article underscores the vital role psychiatric nurses play in early identification, therapeutic interventions, crisis management, and stigma reduction. Challenges such as nurse burnout, stigma, and legal concerns are addressed, along with future directions that involve technological integration, holistic care, and policy advocacy. By consolidating theoretical and practical perspectives, this review aims to support evidence-based psychiatric nursing practice and promote integrated, patient-centered mental health services.